Impact of Hotel Employee’s Emotional Intelligence on Emotional Labor and Job Satisfaction - Sukhragchaa, Amarjargal; Munkhuu, Bilegsaikhan; Badarch, Lkhamtseden (SCAD Independent, 2021)
The previous researches in the Hospitality Industry of Mongolia especially at accommodation service facilities were mainly focused on the quality of hotel services and foreign guest satisfaction and behaviors. There are insufficient researches related to human resources aspects such as psychological problems, work conditions, incentives and career development, job satisfaction. Therefore, the purpose of the research was (1) to carry out a survey related to emotional intelligence, emotional labor and to define job satisfaction among employees who are working for Mongolian upscale hotels, (2) to clear up whether the elements of emotional intelligence have differences depending on its variables and is to explore and to define correlations between variables namely emotional intelligence, emotional labor and job satisfaction, (3) while getting the survey’s outcome to develop more sustainable and beneficial approaches for human resources management and to develop theoretical and practical recommendations. We found that the emotional intelligence of upscale hotel employees has a positive correlation with their emotional labor and job satisfaction. And we also concluded that the frontline employees from the units as front office, housekeeping, food, and beverage perform excellent quality services to the guests from their deepest heart and they have a high level of emotional intelligence.